2017
DOI: 10.31186/jagrisep.16.1.25-32
|View full text |Cite
|
Sign up to set email alerts
|

Profil, Alokasi Dan Pendapatan Tenaga Kerja Pada Perkebunan Kelapa Sawit Rakyat Di Kabupaten Solok Selatan

Abstract: Labor is one of the main inputs in the production activities, including in agriculture. The quality and quantity of labor would have an impact on quality of products. Solok Selatan district is a new district in West Sumatera that has priority program for development of palm oil smallholders. The quality of labor will also determine the sustainability and success of the operational of palm oil smallholders.Field surveys and in-depth interviews had been carried out to find the profile, allocation and labor incom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
1
0
Order By: Relevance
“…Other researchers found that oil palm plantation used less intensive labor. Yulistriani and Mahdi (2017) found that palm oil smallholder used 84.5 working days/ha/ year which means less than 0.25 labor per hectare per day. The high technology used in oil palm production process caused this efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…Other researchers found that oil palm plantation used less intensive labor. Yulistriani and Mahdi (2017) found that palm oil smallholder used 84.5 working days/ha/ year which means less than 0.25 labor per hectare per day. The high technology used in oil palm production process caused this efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…Keterampilan kerja (skill) dan kemampuan kerja sama merupakan etos kerja yang akan menentukan kemampuan tenaga kerja dalam mengkonvergensikan teknologi dan manajemen dari seluruh unit aktivitas kebun dan Pabrik Kelapa Sawit (Tarigan dan Sipayung, 2011). Salah satu hal yang penting agar dapat mencapai produksi maksimal dan berkelanjutan adalah manajemen tenaga kerja perkebunan yang sesuai dengan tugas dan fungsinya (Yulistriani dan Mahdi, 2017).…”
Section: Tenaga Kerjaunclassified